2015
DOI: 10.1016/j.brainres.2015.07.057
|View full text |Cite
|
Sign up to set email alerts
|

S-nitrosoglutathione reduces tau hyper-phosphorylation and provides neuroprotection in rat model of chronic cerebral hypoperfusion

Abstract: We have previously reported that treatment of rats subjected to permanent bilateral common carotid artery occlusion (pBCCAO), a model of chronic cerebral hypoperfusion (CCH), with S-nitrosoglutathione (GSNO), an endogenous nitric oxide carrier, improved cognitive functions and decreased amyloid-β accumulation in the brains. Since CCH has been implicated in tau hyperphosphorylation induced neurodegeneration, we investigated the role of GSNO in regulation of tau hyperphosphorylation in rat pBCCAO model. The rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 85 publications
(133 reference statements)
0
5
0
Order By: Relevance
“…In such an environment, the levels of endogenous redox modulator GSNO are depleted, causing activation of calpains and caspases, leading to neuroinflammation, cell death and functional deficits (Annamalai et al 2015; Corti et al 2014; Khan et al 2016; Khan et al 2011). Supplementation of GSNO in a number of neurodegenerative diseases provides neuroprotection and functional recovery (Khan et al 2016; Khan et al 2012; Khan et al 2011; Khan et al 2005; Won et al 2015). These neuroprotective effects of GSNO may be associated with its reported inhibition of the activity of caspase-3 (Khan et al 2005; Mohr et al 1997) as well as calpains (Annamalai et al 2015; Khan et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In such an environment, the levels of endogenous redox modulator GSNO are depleted, causing activation of calpains and caspases, leading to neuroinflammation, cell death and functional deficits (Annamalai et al 2015; Corti et al 2014; Khan et al 2016; Khan et al 2011). Supplementation of GSNO in a number of neurodegenerative diseases provides neuroprotection and functional recovery (Khan et al 2016; Khan et al 2012; Khan et al 2011; Khan et al 2005; Won et al 2015). These neuroprotective effects of GSNO may be associated with its reported inhibition of the activity of caspase-3 (Khan et al 2005; Mohr et al 1997) as well as calpains (Annamalai et al 2015; Khan et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is reported that S-nitrosylation can inhibit calpain activity, an enzyme responsible for cleavage of p35 to p25 19, 20 . Won et al (2015) reported that S-nitrosoglutathione (GSNO) treatment of purified calpain protein inhibited its activity 21 . Consistent with our findings, Annamalai et al (2015) demonstrated that treatment of APP/PS1 mice with GSNO led to decreased calpain-mediated cleavage of p35 and decreased Cdk5 activity 22 .…”
Section: Discussionmentioning
confidence: 99%
“…In chronically hypoperfused rat brains, GSNO treatment decreased iNOS expression and nitrotyrosine formation. GSNO showed a protective role in iNOS/nitrosative stress‐mediated calpain/tau pathologies (Won et al, ). GSNO reduced Aβ and ICAM‐1/VCAM‐1 levels in the rat brain following chronic cerebral hypoperfusion.…”
Section: Cerebral Hypoperfusion: Therapeutic Approachmentioning
confidence: 99%